GENDER DAN KETAHANAN PANGAN PADA MASYARAKAT PESISIR KOTA AMBON - Pical, Venda Jolanda; Lopulalan, Dortje L Y (Pattimura University, 2022)
Coastal communities in Ambon City have local wisdom and traditions in use of natural resources which have continued to this day and have an impact on household food security, which involves women and men. This study aims to analyze gender equality and food security as well as the factors that influence decision making in the household. The research location is in South Leitimur District, Ambon City, especially in Leahari, Hukurila, Kilang and Naku State. The research method is descriptive qualitative where data is collected from key informants in each country. Data collection techniques through in-depth interviews, making field documentation and field observations. The research data were analyzed using Miles and Huberman qualitative analysis. The results show that gender equality and food security in coastal areas are seen in reproductive and productive activities, access to employment opportunities and forms of social control. The factors that influence household decision making on food security are the division of labor based on the appropriateness of work space, technological innovation in the use of natural resources and social and economic institutions that support decision making in the household. The conclusion of the study shows that gender equality and food security in the coastal areas of Ambon City have been implemented but need to be improved. The research recommendation is that it is necessary to increase the community's capacity for gender equality in development so that it has an impact on improving the welfare of life